2021
DOI: 10.1002/jcp.30262
|View full text |Cite
|
Sign up to set email alerts
|

C1q/tumor necrosis factor‐related protein‐6 attenuates TNF‐α‐induced apoptosis in salivary acinar cells via AMPK/SIRT1‐modulated miR‐34a‐5p expression

Abstract: C1q/tumor necrosis factor‐related protein‐6 (CTRP6) is a newly identified adipokine involved in diverse biological processes. However, its role in salivary glands remains unknown. Here, we demonstrated that CTRP6 was mainly distributed in the nuclei, apicolateral membranes, and cytoplasm of human submandibular glands (SMGs), serous cells of parotid glands, and ducts and apicolateral membranes of serous cells in rats and mice. CTRP6 inhibited the apoptosis rate and reversed the increased levels of cleaved caspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…The rat SMG acinar cell line SMG-C6 (a kind gift from Dr David O. Quissell) was cultured in DMEM/F12 (1:1 mixture) as previously described [23]. In high-glucose (HG) experiments, cells were incubated in normal medium supplemented with D-glucose at a final concentration of 25 mmol/L.…”
Section: Cell and Human Submandibular Gland Tissue Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The rat SMG acinar cell line SMG-C6 (a kind gift from Dr David O. Quissell) was cultured in DMEM/F12 (1:1 mixture) as previously described [23]. In high-glucose (HG) experiments, cells were incubated in normal medium supplemented with D-glucose at a final concentration of 25 mmol/L.…”
Section: Cell and Human Submandibular Gland Tissue Culturementioning
confidence: 99%
“…All participants signed an informed consent document before tissue collection. Fresh SMGs were transported, cut, and incubated with or without HG medium for the indicated times, as described previously [23].…”
Section: Cell and Human Submandibular Gland Tissue Culturementioning
confidence: 99%
“…TNF-induced apoptosis occurs through the binding of TNF type I receptors (TNFR1), which contain death domains that transmit apoptotic signals through caspase activation ( 160 ). In addition, TNFα significantly increased the levels of caspase 3, 8, 9 and cytochrome C, leading to a decrease in the level of Bcl-2 and induced apoptosis of SMG-C6 cells and human SMG tissues ( 161 ). Caspase 3 is considered the most important executor of apoptosis, and caspase 8 initiates the death receptor pathway of apoptosis.…”
Section: The Role Of Key Inflammatory Factorsmentioning
confidence: 99%
“…To determine the role of these miRNAs in TNFα -induced acinar cell apoptosis, real-time PCR was used to measure their expression levels after cells were incubated with TNFα for a specified period of time. The results showed that TNFα could induce significantly increased levels of Mir-34a-5p, Mir-34a-3p, Mir-200b-5p and Mir-200b-3p simultaneously, while leT-7a-5P expression remained unchanged ( 161 ).…”
Section: The Role Of Key Inflammatory Factorsmentioning
confidence: 99%
“…It has been reported that miR-34a increases with aging in vessels and induces senescence and the acquisition of the senescence-associated secretory phenotype (SASP) in ECs 7 9 . SIRT1 has been revealed that it could be regulated by miR-34a 10 . miR-34a inhibits SIRT1 through a miR-34a binding site with the 3’UTR of SIRT1 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%